Mechanistic Insights into NO Releasing by Functionalized Carbon Quantum Dots: A DFT Study - Souza-Silva, Henrique Rodrigues [UNESP]; Gomes, Orisson Ponce [UNESP]; Dionizio, João Pedro [UNESP]; Bégué, Didier; Lisboa-Filho, Paulo Noronha [UNESP]; Batagin-Neto, Augusto [UNESP] (American Chemical Society (ACS), 2025)
The development of carbon quantum dots (CQDs) for photoresponsive nitric oxide (NO) delivery is a rapidly advancing field, with experimental reports demonstrating promising release under visible light irradiation. However, a mechanistic understanding of the photolytic process, the explicit role of CQD functionalization, and the influence of key physiological variables such as pH has been lacking, hindering rational design. This study aims to unravel the atomistic details of the NO release mechanism in functionalized CQD systems. Using density functional theory (DFT) and time-dependent DFT (TD-DFT) calculations, we systematically investigated a model system (CQDCA CYS+TPP···NO) to probe ground-state reactivity, protonation effects, and excited-state properties. Our results reveal that cysteine deprotonation is a critical effect for S-NO bond formation. TD-DFT calculations evidence a low-energy SNO-localized excited state with predominant n → π* character, which drives direct photoinduced electron transfer from sulfur to nitrogen, weakening the S-NO bond and rationalizing the experimental photodynamic response. While very acidic conditions can destabilize the system, it remains stable under physiological pH. These findings provide a mechanistic framework that clarifies the synergistic roles of the CQD, cysteine, TPP, and NO moieties on the nanocomposite, offering foundational principles for engineering next-generation CQD-based platforms with enhanced stability, controlled release efficiency, and reduced off-target effects for biomedical applications.